2020
DOI: 10.1155/2020/4023787
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Stage 1 Hypertension Defined by the 2017 ACC/AHA Guideline with Stroke and Its Subtypes among Elderly Chinese

Abstract: Background. The 2017 American College of Cardiology and American Heart Association hypertension guideline updated stage 1 hypertension definition as systolic blood pressure range from 130 to 139 mmHg or diastolic blood pressure from 80 to 89 mmHg. However, the association of stage 1 hypertension with stroke and its subtypes among the older population in rural China remains unclear. Methods. This population-based cohort study consisted of 7,503 adults aged ≥60 years with complete data and no cardiovascular dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(40 reference statements)
2
1
0
1
Order By: Relevance
“…Starting at a systolic blood pressure level of 90 mm Hg, there is a 53% higher risk for atherosclerotic cardiovascular disease for each 10-mm Hg systolic blood pressure increase [63,64]. These results were consistent with other studies conducted in Iran and globally that showed that the association between HTN and a history of CVD is continuous and independent of other risk factors [5,15,40,65].…”
Section: Plos Onesupporting
confidence: 89%
“…Starting at a systolic blood pressure level of 90 mm Hg, there is a 53% higher risk for atherosclerotic cardiovascular disease for each 10-mm Hg systolic blood pressure increase [63,64]. These results were consistent with other studies conducted in Iran and globally that showed that the association between HTN and a history of CVD is continuous and independent of other risk factors [5,15,40,65].…”
Section: Plos Onesupporting
confidence: 89%
“…The results obtained from the study by Saju et al in India and the study by Gao et al in China showed a direct and significant relationship among smoking, lack of physical activity, diabetes, and ischemic heart disease and blood pressure. In addition, in the present study, the above-mentioned factors had significant relationships with blood pressure [24,25]. Rabi stated that since most blood pressure factors are modifiable, lifestyle and diet modifications can be considered as the most important and effective measures for the prevention and subsequent reduction of nasal side effects of hypertension.…”
Section: Discussionsupporting
confidence: 49%
“…29 Unlike the current results, stage 1 HTN has been reported as a risk factor for CVD in some cohort studies. 27,30 In the study conducted by Qi et al, 19 the HRs for CVD, CHD, and stroke associated with stage 1 HTN were 1.78, 1.77, and 1.79, respectively. A recent meta-analysis of cohort studies also found that CVD was more common in stage 1 HTN compared to normal BP (HR: 1.38, 95% CI 1.28-1.49).…”
Section: Discussionmentioning
confidence: 97%